The Analysis Added Value of Liquid Palm Sugar in Maabhodo Village Kontunaga District Muna Regency (Case Study of Ino Palma Aren Sejahtera Group) - Elfa Elfa; Yusna Indarsyih; Samsul Alam Fyka (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
This study aims to determine the process of processing palm sap into liquid palm sugar and analyze the value-added in the business of processing palm sap into liquid palm sugar. The research area was determined purposively, considering that a group succeeded in processing palm sap into liquid palm sugar at that location. This research starts from the time the research title is accepted until it is completed, namely in December 2021 to January 2022. The data collection time is one month, from October to November 2021. The sampling method uses the saturated sample method with a sample of 20 people. The data analysis method used is the added value of the Hayami method and descriptive analysis. The results showed that processing palm sap into liquid palm sugar started by providing raw materials, filtering/filtration, cooking juice, and packaging. The added value obtained from processing palm sap into liquid palm sugar is IDR98.11/ml or IDR98.110/liter. The amount of added value is obtained from the difference between the value of the product and the price of raw materials, and the contribution of other inputs used in processing palm sap. The product value is IDR125/ml or IDR125.000/liter with raw material prices of IDR8.34/ml or IDR8.340/liter with a conversion factor of 0.625. This condition impacts the added value ratio of palm sap processing into liquid palm sugar of 78.48 (a high percentage). The results also show that the employee benefits are IDR25/ml or IDR25.000/liter with the share of labor 25.48% with a profit of IDR73